Analisis Kondisi Fisik Atlet Club Bola Voli Putri Di Kota Bengkulu Tahun 2020 - Pipin Silpina; Tono Sugihartono; Ari Sutisyana (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to determine the differences in pliometric training of single leg speed hops and double leg speed hops on the ability of squat style long jump in SMA Negeri 08 Bengkulu Utara. The type of research used in this study was quasi-experimental. The sample in this study was students at SMA Negeri 08 Bengkulu Utara which numbered 50 students. The statistical analysis used is the t test. The results of the t-test analysis of the comparison calculation between the final results of the two groups turned out to have a significant difference. The calculation results state that tcount of 3.02 is greater than ttable 2.069 with the level of ? = 0.05, so it can be concluded that there are differences in the influence of the single leg speed hop pliometric exercise and double leg speed hop hops on the ability of squat style long jump.